GE_GERICHTE P/18056/2012 vom 21. März 2014 - GE Cour de justice (2014)
PLAIGNANT; AYANT DROIT ÉCONOMIQUE; GESTION DÉLOYALE; ABUS DE CONFIANCE; FIDUCIANT; DOMMAGE DIRECT; ENQUÊTE PÉNALE; COMPLÉMENT | CPP.118; CPP.115; CP.138; CP.158